PEMANFAATAN FOTO UDARA UNTUK PEMETAAN PERMUKIMAN KUMUH DI KECAMATAN BOJONGLOA KALER, KOTA BANDUNG - Fajar Eko Purnomo, - (2021)
ABSTRACT Bojongloa Kaler sub-district is classified as having a high population density of 40,061 people/Km2 of an area of only 3.03 Km2. The purpose of this study was to map the distribution of slums using aerial photographic images and analyze the factors that most influence the distribution of slums in the District of Bojongloa Kaler. The method used in this study is a survey method using a GIS analysis approach, namely the appraisal method using seven parameters to determine slum settlements. Identification of the distribution of slum levels was carried out by visual interpretation of aerial photos and field surveys, then each parameter was rated and then overlaid to produce a map of the distribution of slums. The results of the study were divided into four classes, namely heavy slums (60.41%), medium slums (30.9%), light slums (3.37%) and non-slums (5.52%). The results of the analysis of the most influencing factors are high population density. Accuracy test results for spatial suitability (92.98%), distance between buildings (91.22%), building density (87.71%), road conditions (94.72%). The results of the accuracy test are classified as good so that it proves that the interpretation results are fairly accurate with the conditions in the field. In the future, the government must be more careful and strict in granting a Building Permit (IMB). The use of imagery is recommended to use images such as worldview-2, worldview-3, or aerial photo images to make it easier to interpret the parameters obtained from the image. Keywords : Slums Areas, Aerial Photographs, SIG, Interpretation